2018
DOI: 10.1017/s0033291718003604
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of neuropsychological, social cognitive, and olfactory functioning in the behavioral and language variants of frontotemporal dementia

Abstract: BackgroundThough meta-analyses of neuropsychological and social cognitive deficits in behavioral variant frontotemporal dementia (bvFTD) have been conducted, no study has comprehensively characterized and compared the neuropsychological, social cognitive, and olfactory profiles in the behavioral and language variants of FTD.MethodsOur search yielded 470 publications meeting inclusion criteria representing 11 782 FTD patients and 19 451 controls. For each domain, we calculated Hedges’ g effect sizes, which repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…The impairment in financial capacity may be explained by the deficit in risk judgment and decision-making [61,62]. Several studies suggest social cognition could be a sensitive predictor of MCI and an index to identify dementia from normal aging individuals [63-65]. Therefore, to increase the ecological utility, the experts agreed to include social cognition in the CNCB.…”
Section: Discussionmentioning
confidence: 99%
“…The impairment in financial capacity may be explained by the deficit in risk judgment and decision-making [61,62]. Several studies suggest social cognition could be a sensitive predictor of MCI and an index to identify dementia from normal aging individuals [63-65]. Therefore, to increase the ecological utility, the experts agreed to include social cognition in the CNCB.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive supranuclear palsy, CBS, and svPPA are primarily associated with FTLD-tau, but in bvFTD, the underlying pathology is heterogenous, and therefore, the relationship between clinical presentation and pathology is poorly understood. To date, cognitive impairments, including memory, executive functioning, visuo-construction, language, and behavioral changes have been associated with tau pathology or MAPT mutation (Hu et al, 2007;Grossman et al, 2008;Mendez et al, 2013;Kamath et al, 2019;Poos et al, 2020;Benussi et al, 2021), while social cognition impairments were found in patients with C9orf72 (Russell et al, 2020;Franklin et al, 2021).…”
Section: Pathology Of Ftldmentioning
confidence: 99%
“…Initial reports of symptoms in PPA have typically focused on analyzing language function. However, neuropsychological testing has revealed additional executive impairment in PPA variants (Kamath et al, 2019(Kamath et al, , 2020. Individuals with nfvPPA have shown executive deficits on verbal tasks of working memory, verbal fluency, as well as on non-verbal tasks of mental flexibility and abstract reasoning (Macoir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%